China public emotion analysis under normalization of COVID-19 epidemic: Using Sina Weibo - Zhang, Fa; Tang, Qian; Chen, Jian; Han, Na (Frontiers in Psychology, 2023)
The prevention and control of COVID-19 epidemic in China has entered a normalization phase. Understanding public sentiment and concern is the basis for evaluating and improving public health strategies. This paper established a fine-grained emotion classification model to make emotion annotation about 32,698 Sina Weibo posts related to COVID-19 prevention and control from July to August 2022. The Dalian University of Technology (DLUT) emotion classification system was adjusted to form 4 pairs of 8 categories of bidirectional emotions: good-disgust, happy-sadness, anger-fear, and surprise-anticipation. A lexicon-based method was designed to classify the emotions of Weibo posts. Based on the marked dataset, we analyzed the public sentiments and emotions. The results showed that positive sentiment accounted for 51%, negative for 24%, and neutral for 25%. The positive sentiment was dominated by good and joy emotions, and the negative sentiment was dominated by fear and disgust emotions. The proportion of positive sentiment in official Weibo (government departments and official media) is significantly higher than that in personal. Official Weibo have a weak guiding effect on personal in terms of positive sentiment, and almost completely synchronized in terms of negative sentiment. LDA was performed on the two negative emotions, fear and disgust, in personal posts. We found that fear was mainly related to COVID-19 infection and death, control of people with positive nucleic acid tests, and the outbreak of local epidemics; while disgust was mainly related to the long-term existence of the epidemic, charges for nucleic acid tests, non-implementation of prevention and control measures, and the occurrence of foreign epidemics. These findings suggested that Chinese attitude toward epidemic prevention and control is generally positive and optimistic, but there is also a certain proportion of fear and disgust. We hope that this study could help public health administrators to evaluate the effectiveness of measures and achieve precise prevention and control of COVID-19.